The Effect of malnutrition on Growth of Pre-school Children: A Narrative Review - Ms. Snehapriya; Prof. (Dr.) Sunil Kumar Dular; Ms. Deepa Mukherjee (The Bioscan, 2024)
Background: In numerous developing nations, stunting, underweight and micronutrients deficiencies in children often stem from poor nutrition and infections experienced in early childhood, coupled with a diet that fails to meet the high nutritional needs of rapid growth during childhood. Objective: to gain insight into the effects of malnutrition during this crucial stage of growth is vital for creating interventions that enhance health outcomes and mitigate long-term consequences. The review underscores the urgent need for effective interventions and policies to combat early childhood malnutrition Method: This review explores the effects of malnutrition on the growth and development of preschool-aged children, drawing insights from 35 studies. It emphasizes the influence of malnutrition on physical growth, developmental milestones, health outcomes, and the underlying mechanisms driving these impacts. Manual searches were conducted in additional relevant journals and the reference lists of primary articles. Conclusion: The impact of malnutrition on school-going children is profound and multifaceted, affecting their physical growth, cognitive development, and overall well-being. Addressing malnutrition is critical for ensuring that children reach their full potential, both in school and in life.